I am not your negro : a companion edition to the documentary film directed by Raoul Peck / by James Baldwin ; compiled and introduced by Raoul Peck. - Baldwin, James, 1924-1987 (Vintage Books, 2017)
Transcript of the documentary film, I am not your negro, by Raoul Peck composed of unpublished and published writings, interviews, and letters by James Baldwin on the subject of racism in America.